An anion-doped lead-free piezoelectric ceramic, preparation and application thereof
Patent Information
- Application Number
- CN202611478693.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
然而,KNN基材料的铁电类型单一,通常为正常铁电体,介电温谱呈现尖锐峰形,导致其在不同应用场景下面临以下问题:压电器件虽具有较高压电常数,但温度稳定性差,难以在宽温区稳定工作;介电器件(电容器)因尖锐介电峰导致相对介电常数随温度剧烈变化,无法满足温度稳定性要求;应变器件(驱动器)因电致应变随温度变化显著、应变滞后大,难以在宽温区实现精密位移控制
(1)本发明通过阴离子高掺杂在KNN基体中构建弛豫铁电结构的方法,实现了对KNN基材料宽温区介电性能、压电性能、应变性能等宽温区功能物性的可调控,与现有依赖复杂阳离子掺杂的方法形成本质区别,为KNN基材料的功能化提供了新思路。
Smart Images

Figure CN122977843A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of piezoelectric ceramics technology, and in particular to an anion-doped lead-free piezoelectric ceramic and its preparation and application. Background Technology
[0002] Piezoelectric ceramics are a class of functional materials capable of converting mechanical energy into electrical energy, and are widely used in electronic components such as transducers, sensors, and actuators. Since the advent of lead zirconate titanate (PZT) ceramics, lead-based piezoelectric ceramics have long dominated the market due to their excellent piezoelectric properties and good temperature stability. However, lead-based ceramics contain more than 60% lead, posing serious hazards to the environment and human health during production, use, and disposal. Therefore, developing high-performance lead-free piezoelectric ceramics has become an important research direction in the field of piezoelectric materials.
[0003] Among numerous lead-free piezoelectric ceramic systems, potassium sodium niobate (KNN)-based ceramics are considered one of the most promising PZT alternatives due to their high piezoelectric response, high Curie temperature, and environmentally friendly properties. However, KNN-based materials exhibit a single ferroelectric type, typically being normal ferroelectrics, with sharp peaks in their dielectric temperature spectrum. This leads to the following problems in different applications: piezoelectric devices, while possessing high piezoelectric constants, suffer from poor temperature stability, making stable operation over a wide temperature range; dielectric devices (capacitors) experience drastic temperature changes in their relative permittivity due to sharp dielectric peaks, failing to meet temperature stability requirements; and strain devices (actuators) exhibit significant temperature variations in electro-strain and large strain hysteresis, making precise displacement control difficult over a wide temperature range.
[0004] The core reason for the above problems is that KNN-based materials lack controllable structural modulation methods, making it impossible to systematically regulate their wide-temperature-range functional properties according to application requirements. Existing technologies mainly rely on complex A-site and B-site cation doping, but a clear approach to wide-temperature-range property regulation guided by structural design has not yet been established. Summary of the Invention
[0005] The purpose of this invention is to provide anion-doped lead-free piezoelectric ceramics, their preparation and application. By constructing a relaxor ferroelectric structure in a potassium sodium niobate ceramic matrix through anion doping, the functional properties such as dielectric properties, piezoelectric properties, and electrostrain properties can be tunable over a wide temperature range.
[0006] To achieve the above objectives, the present invention provides anion-doped lead-free piezoelectric ceramics, which have a relaxor ferroelectric structure constructed by anion doping; their general chemical formula is 0.93K. 0.50 Na 0.44 Li 0.06 NbO3-0.07CaAO 3- x F2x A is Zr. x The molar percentage of CaF2 replacing CaCO3, 0 < x ≤100%.
[0007] The anion of this invention is F - Doping introduces local compositional inhomogeneity and lattice distortion into the KNN matrix, disrupting long-range ferroelectric order and thus constructing a relaxor ferroelectric structure. The relaxation degree of this structure is continuously adjustable with the concentration of anion doping.
[0008] This invention also provides a method for preparing the above-mentioned anion-doped lead-free piezoelectric ceramic, comprising the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder. S2. The raw material powder obtained in S1 is pre-calcined at 750~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1080~1150℃ for 3~6h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
[0009] Preferably, in S1 and S2, the dispersion medium for the rolling ball mill is anhydrous ethanol, and the rolling ball milling time is 4-12 hours.
[0010] Preferably, in S3, granulation is carried out by adding a polyvinyl alcohol solution to the calcined powder for granulation, wherein the concentration of the polyvinyl alcohol solution is 6~10wt%.
[0011] Preferably, in step S3, the pressing is performed by using an electric tablet press to compress the granulated powder into tablets, with the pressure of the electric tablet press being 8-12 MPa.
[0012] Preferably, in S3, the temperature for discharging the adhesive is 750-850℃, and the discharging time is 80-100min.
[0013] Preferably, in S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~6kV / mm, and the electric field polarization time is 20~40min.
[0014] This invention also provides an application of the above-mentioned anion-doped lead-free piezoelectric ceramic in the fabrication of wide-temperature-range transducers.
[0015] Therefore, the present invention, employing the above-mentioned anion-doped lead-free piezoelectric ceramic and its preparation and application, has the following beneficial effects: (1) The present invention constructs a relaxed ferroelectric structure in the KNN matrix by high anion doping, which realizes the controllability of the wide temperature range functional properties of KNN-based materials such as dielectric properties, piezoelectric properties, and strain properties. This is fundamentally different from the existing methods that rely on complex cation doping, and provides a new idea for the functionalization of KNN-based materials.
[0016] (2) This invention successfully constructed a relaxor ferroelectric structure in a KNN matrix through anion doping. The degree of construction of this structure varies with the anion doping concentration. x The structure exhibits a continuously adjustable pattern: as the amount of anion doping increases, the ferroelectric structure gradually transforms into a partially relaxed ferroelectric structure, and finally presents a fully relaxed ferroelectric structure. This continuously adjustable relaxation structure construction pattern lays the structural foundation for the controllable design of functional properties over a wide temperature range.
[0017] (3) This invention adjusts the fluorine ion doping concentration x This invention enables precise control over the degree of relaxation ferroelectric structure construction, thereby obtaining functional property combinations suitable for applications across a wide temperature range. The lead-free piezoelectric ceramic material prepared by this invention exhibits a flat dielectric response, stable piezoelectric properties, and strain properties over a wide temperature range, providing a novel design approach for wide-temperature-range functional property control of KNN-based lead-free piezoelectric ceramics. Furthermore, this lead-free piezoelectric ceramic contains no lead, making it an environmentally friendly material with a very wide range of applications.
[0018] (4) The method of constructing a relaxed ferroelectric structure in the KNN matrix by high anion doping in this invention can provide new ideas for structural design and wide-temperature-range functional property control in the field of lead-free piezoelectric materials.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 These are the XRD patterns of the lead-free piezoelectric ceramics of Examples 1-4 and Comparative Example 1 of the present invention; Figure 2 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Comparative Example 1 of the present invention with temperature. Figure 3 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Embodiment 1 of the present invention with temperature; Figure 4 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic as a function of temperature in Embodiment 2 of the present invention; Figure 5This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Embodiment 3 of the present invention with temperature; Figure 6 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic as a function of temperature in Embodiment 4 of the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0022] This invention provides an anion-doped lead-free piezoelectric ceramic, which has a relaxor ferroelectric structure constructed by anion doping; its general chemical formula is 0.93K. 0.50 Na 0.44 Li 0.06 NbO3-0.07CaAO 3-x F 2x A is Zr. x The molar percentage of CaF2 replacing CaCO3, 0 < x ≤100%. The "-" in the general formula indicates a homogeneous compound formed by multi-component doping.
[0023] This invention introduces lithium ions (Li) into potassium sodium niobate ceramics. + A-site doping is performed, and a second component of the perovskite structure, such as calcium zirconate (CaZrO3), calcium hafnium oxide (CaHfO3), or calcium stannate (CaSnO3), is introduced for cation modification. After sintering, a piezoelectric ceramic structure with multiphase coexistence at room temperature is obtained. This multiphase coexistence structure can refine ferroelectric domains, reduce polarization barriers, and thus optimize piezoelectric performance.
[0024] This invention further uses calcium fluoride (CaF2) to replace calcium carbonate (CaCO3) in traditional raw materials, thereby achieving the desired effect of fluoride ion concentration (F2). - ) for oxygen ions (O 2-The substitution of fluoride ions at lattice sites, i.e., anion doping, is a process where fluoride ions, compared to oxygen ions, carry less negative charge and are more electronegative. Their substitution introduces positively charged defects into the lattice and strengthens the chemical bond strength with the coordinating cation, inducing stronger local lattice distortion. This local lattice distortion disrupts the long-range ferroelectric order in the perovskite structure, refining the ferroelectric domain size and forming polar nanodomains. Simultaneously, the introduction of fluoride ions alters the hybridization strength between the B-site cation and oxygen ion, leading to a non-uniform distribution of polarization responses in different regions. This results in macroscopically exhibiting typical characteristics of relaxor ferroelectrics: a broadened dielectric peak in the dielectric temperature spectrum, significant frequency dispersion, and a shift in the dielectric peak position towards higher temperatures with increasing frequency. By adjusting the fluoride ion doping concentration… x This allows for precise control over the degree of local lattice distortion and the density of polar nano-regions, thereby enabling controllable design of the degree of relaxation ferroelectric structure construction. This relaxation ferroelectric structure exhibits a broadened dielectric peak and significant frequency dispersion characteristics, ensuring stable relative permittivity, piezoelectricity, and electrostrain properties across a wide temperature range. This achieves the structural transformation of KNN-based materials from normal ferroelectrics to relaxation ferroelectrics.
[0025] The molar percentage of each component in the lead-free piezoelectric ceramic of this invention needs to be strictly controlled; wherein, the main phase component "0.93K" 0.5 Na 0.44 Li 0.06 The atomic ratios of K, Na, Li, Nb, and O in “NbO3-0.07CaAO3” should be 0.50, 0.44, 0.06, 1.00, and 3, respectively, based on valence balance. The atomic ratios of Ca, A (where A is Zr), and O in the component “CaAO3” should be 1, 1, and 3. When these ratios deviate significantly, the phase structure of the ceramic changes noticeably, and the domain structure changes accordingly, leading to a decrease in piezoelectric properties. If the ratios deviate considerably, excess elements can easily form impurity phases during the doping process, remaining in the multiphase piezoelectric ceramic structure and further worsening the piezoelectric properties.
[0026] Preferably, in the general chemical formula x The value range is 30% < x ≤100%.
[0027] Further selection, x The value range is 50% < x ≤100%.
[0028] For the next best selection, 50% ≤ x When the content is ≤70%, lead-free piezoelectric ceramics exhibit a partially relaxed structure. x When the lead content is 100%, the lead-free piezoelectric ceramic is a fully relaxed ferroelectric structure.
[0029] In this invention, whenx When the lead content is 0%, no fluorine ion doping is introduced, and the piezoelectric properties of the lead-free piezoelectric ceramic are relatively low, with the dielectric temperature spectrum exhibiting the sharp peak shape of a normal ferroelectric material; as the lead content increases... x With increasing fluoride ion substitution, the relaxor ferroelectric structure is gradually constructed, the dielectric peak gradually broadens, frequency dispersion appears, and the temperature stability of dielectric and piezoelectric properties is significantly improved; when x When the lead-free piezoelectric ceramic reaches 100%, it constructs a fully relaxor ferroelectric structure, exhibiting a flat dielectric response and stable strain properties over a wide temperature range.
[0030] Relaxor ferroelectric structures exhibit the following typical characteristics: a broadened dielectric peak in the dielectric temperature spectrum, significant frequency dispersion (the dielectric peak position shifts towards higher temperatures with increasing frequency), and the dielectric peak shift with frequency conforms to Vogel-Fulcher relaxation behavior. As the degree of relaxation increases, the Curie temperature ( T c The dielectric peak near the vicinity is significantly broadened. T c The ratio of the relative permittivity at room temperature to the relative permittivity at room temperature ( ε r ( T c ) / ε r (RT) from 4.57 of normal ferroelectrics ( x =0%) decreased to 2.69 for fully relaxed ferroelectrics. x =100%), indicating that the order of long-range ferroelectricity is disrupted and the relaxation characteristics are enhanced.
[0031] This invention also provides a method for preparing the above-mentioned anion-doped lead-free piezoelectric ceramic, comprising the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder.
[0032] S2. The raw material powder obtained in S1 is pre-calcined at 750~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1080~1150℃ for 3~6h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
[0033] Preferably, in S1 and S2, the dispersion medium for the rolling ball mill is anhydrous ethanol, and the rolling ball milling time is 4-12 hours.
[0034] Even more preferably, the rolling ball mill uses a nylon grinding jar and zirconium balls.
[0035] In a further preferred embodiment, in S2, pre-firing involves placing the raw material powder into an alumina crucible for pre-firing.
[0036] Preferably, in step S3, granulation involves adding a polyvinyl alcohol solution to the calcined powder obtained in step S2 for granulation. The concentration of the polyvinyl alcohol solution is 6-10 wt%. By controlling the concentration and amount of the polyvinyl alcohol solution within the above range, this invention can improve the powder flowability and green body mechanical strength, and help obtain a green body with a more uniform density. If the concentration of the polyvinyl alcohol solution is less than 6 wt%, the sample is prone to being misshapen, making it impossible to obtain lead-free piezoelectric ceramic material. If the concentration of the polyvinyl alcohol solution is greater than 10 wt%, the piezoelectric performance is prone to decrease or the sample may contain pores, resulting in the inability to obtain a dense lead-free piezoelectric ceramic material.
[0037] In some specific embodiments of the present invention, the concentration of the polyvinyl alcohol solution is 10 wt%.
[0038] Preferably, in step S3, the pressing is performed by using an electric tablet press to compress the granulated powder into tablets, with the pressure of the electric tablet press being 8-12 MPa.
[0039] More preferably, the sheet shape obtained by pressing includes one of the following: round, square, and oval; during pressing, the granulated powder is placed in a mold with a cavity.
[0040] Preferably, in S3, the temperature for discharging the adhesive is 750-850℃, and the discharging time is 80-100min.
[0041] Preferably, in S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~6kV / mm, and the electric field polarization time is 20~40min.
[0042] This invention also provides an application of the above-mentioned anion-doped lead-free piezoelectric ceramic in the fabrication of wide-temperature-range transducers.
[0043] Example 1 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.7 F 0.6 ,in x It is 30%.
[0044] The above-mentioned method for preparing anion-doped lead-free piezoelectric ceramic includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 8 hours, dried and mixed evenly to obtain the raw material powder.
[0045] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 850℃ for 6 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0046] S3. Add an 8wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 10MPa. Then, remove the binder at 800℃ for 90min to obtain a ceramic green body.
[0047] S4. The ceramic blank obtained in S3 is sintered at 1120℃ for 4 hours to obtain a piezoelectric ceramic body.
[0048] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then placed in silicone oil at 30℃. Under an electric field strength of 4kV / mm, the ceramic body is polarized for 30 minutes to obtain lead-free piezoelectric ceramic.
[0049] Example 2 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.5 F 1.0 ,in x The content is 50%. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic is the same as that in Example 1.
[0050] Example 3 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.3 F 1.4 ,in x The content is 70%. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic is the same as that in Example 1.
[0051] Example 4 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.0 F 2.0 ,in x The result is 100%. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic is the same as that in Example 1.
[0052] Example 5 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.7 F 0.6 ,in x It is 30%.
[0053] The above-mentioned method for preparing anion-doped lead-free piezoelectric ceramic includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 4 hours, dried and mixed evenly to obtain raw material powder.
[0054] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 750℃ for 8 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0055] S3. Add a 6wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 8MPa. Then, remove the binder at 750℃ for 80min to obtain a ceramic green body.
[0056] S4. The ceramic blank obtained in S3 is sintered at 1080℃ for 6 hours to obtain a piezoelectric ceramic body.
[0057] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic obtained in S4, and then placed in silicone oil at 25℃. Under an electric field strength of 2kV / mm, the ceramic is polarized for 40 minutes to obtain lead-free piezoelectric ceramic.
[0058] Example 6 This invention provides an anion-doped lead-free piezoelectric ceramic with the chemical formula: 0.93K. 0.5 Na 0.44 Li 0.06 NbO3-0.07CaZrO 2.7 F 0.6 ,in x It is 30%.
[0059] The above-mentioned method for preparing anion-doped lead-free piezoelectric ceramic includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 12 hours, dried and mixed evenly to obtain raw material powder.
[0060] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 950℃ for 4 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0061] S3. Add a 10wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 12MPa. Then, remove the binder at 850℃ for 100min to obtain a ceramic green body.
[0062] S4. The ceramic blank obtained in S3 is sintered at 1150℃ for 3 hours to obtain a piezoelectric ceramic body.
[0063] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic obtained in S4, and then placed in silicone oil at 35℃. Under an electric field strength of 6kV / mm, the ceramic is electrically polarized for 20 minutes to obtain lead-free piezoelectric ceramic.
[0064] Comparative Example 1 The difference from Example 1 is that, x When the K0 is zero, a lead-free piezoelectric ceramic with the chemical formula 0.93K is obtained. 0.5 Na 0.44 Li 0.06 The NbO3-0.07CaZrO3, and the rest are the same as in Example 1.
[0065] The lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 were characterized by X-ray diffraction, and the results are as follows: Figure 1As shown, Examples 1-4 and Comparative Example 1 all have 7 characteristic peaks between 20-70°, which are
[100] ,
[110] ,
[002] ,
[200] ,
[210] ,
[211] , and
[220] as the angle increases, indicating that the lead-free piezoelectric ceramic of the present invention is a perovskite ceramic. A split peak appears near 45-46°, namely the
[002] and
[200] peaks, with their peak intensity ratio deviating from 1:2 or 2:1, excluding pure T or O phases, indicating that the lead-free piezoelectric ceramic has a multiphase coexistence structure; in the lead-free piezoelectric ceramic... x Content ≤ 0 x The peak shapes of the XRD patterns within the ≤100% range are basically consistent, indicating that the lead-free piezoelectric ceramic structure of the present invention is relatively stable and always exhibits multiphase coexistence.
[0066] The lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 were left to stand in air for 24 hours and then used as samples for electrical performance testing according to IEEE standards. The results are shown in Tables 1-4.
[0067] Table 1. Electrical properties and Curie temperature of Examples 1-4 and Comparative Example 1
[0068] Note: d 33 It is the piezoelectric constant; ε r tan is the relative permittivity; δ Dielectric loss; T c The Curie temperature.
[0069] Table 1 shows that replacing calcium carbonate (CaCO3) in the traditional raw material with calcium fluoride (CaF2) achieves the desired effect of increasing fluoride ion concentration (F2). - ) for oxygen ions (O 2- After lattice site substitution, the electrical properties of lead-free piezoelectric ceramic materials change with the concentration of fluorine ions. x It exhibits a significant and controllable pattern of change. When x When the doping concentration is 0% (without fluorine ions), the lead piezoelectric ceramic exhibits a normal ferroelectric structure with a piezoelectric constant of 0%. d 33 The ratio is 230 pC / N, and the relative permittivity is 1483; with increasing fluorine ion doping concentration, a relaxor ferroelectric structure is gradually constructed, when... x At 30%, the material still has a normal ferroelectric structure, but it is in the precursor stage of the transition from normal ferroelectric to relaxor ferroelectric. The piezoelectric constant reaches its maximum value of 330 pC / N, the relative permittivity increases to 1658, the dielectric loss decreases to 0.024, and the Curie temperature... T cAn increase to 33°C indicates that this component is in the precursor stage of the transition from normal ferroelectric to relaxor ferroelectric; when x When the concentration is increased to 50%, 70%, and 100%, the material gradually transforms into a fully relaxed ferroelectric structure. Although the piezoelectric constant and relative permittivity decrease, the Curie temperature continues to rise to 336℃, the dielectric temperature spectrum shows a broadening characteristic, and the dielectric temperature stability is significantly improved.
[0070] Table 2. Piezoelectric constants of Examples 1-4 and Comparative Example 1 d 33 Temperature stability
[0071] Note that RT represents room temperature. d 33 (300℃) / d 33 (RT) represents the piezoelectric constant retention rate.
[0072] As shown in Table 2, when x When =0%, the piezoelectric constant retention rate at 300℃ is only 46%; when x When the piezoelectric constant retention rate is 30%, it increases to 57%; when x When the piezoelectric constants are 50%, 70%, and 100%, the piezoelectric constant retention rates increase to 74%, 77%, and 80%, respectively. This indicates that the construction of the relaxor ferroelectric structure significantly improves the high-temperature piezoelectric stability of lead-free piezoelectric ceramics.
[0073] Table 3 Electrostrain of Examples 1-4 and Comparative Example 1 S Temperature stability
[0074] Note that RT represents room temperature. S (300℃) / S (RT) represents the strain retention rate.
[0075] As shown in Table 3, when x When the strain retention rate is 0%, the strain retention rate of lead-free piezoelectric ceramics at 300℃ is only 48%; when x When the lead content is 30%, the strain retention rate of lead-free piezoelectric ceramics increases to 51%; when x When the strain retention rates are 50%, 70%, and 100%, the strain retention rates of lead-free piezoelectric ceramics increase to 72%, 78%, and 82%, respectively. This indicates that the construction of the relaxor ferroelectric structure significantly improves the high-temperature strain stability of lead-free piezoelectric ceramics.
[0076] Table 4. Relative permittivity of Examples 1-4 and Comparative Example 1 ε r Temperature stability
[0077] Note that RT represents room temperature. T c The Curie temperature.
[0078] As shown in Table 4, with the increase of fluorine ion doping concentration... x The increase, T c The dielectric peaks in the vicinity are significantly broadened. ε r ( T c ) / ε The ratio of r(RT) from x =0% of 4.57 dropped to x =30% of 4.19 x =50% of 2.96 x =70% of 2.71 x =100% 2.69. The continuous decrease in this ratio indicates the gradual formation of a relaxor ferroelectric structure, the disruption of long-range ferroelectric order, and an increase in the broadening of the dielectric peak. Simultaneously, the relative permittivity retention rate at 500℃ increases from... x =0% increased to 66% x =99% of 100% indicates that the fully relaxor ferroelectric structure has a nearly constant dielectric response in an ultrawide temperature range of 25-500℃.
[0079] The relative permittivity of the samples was measured in real time at test frequencies of 0.1 kHz, 1 kHz, 10 kHz, and 100 kHz, with the temperature increased uniformly according to the programmed sequence. The relative permittivity-temperature curves were then plotted. Figures 2 to 6 As shown, with the fluorine ion doping concentration... x With the increase of , the dielectric temperature spectrum of the material changes significantly: when x When the piezoelectric constant is 0% (Comparative Example 1), the dielectric temperature spectrum exhibits the sharp peak shape of a normal ferroelectric material. Tables 2 and 3 show that the piezoelectric constant and strain properties decrease rapidly with increasing temperature, with retention rates of 46% and 48% at 300℃, respectively. x When the concentration was 30% (Example 1), the dielectric temperature spectrum still showed the sharp peak shape of normal ferroelectrics, but the piezoelectric constant increased to a maximum of 330 pC / N, and the Curie temperature increased to 330 °C, indicating that this composition was in the precursor stage of the transition from normal ferroelectrics to relaxor ferroelectrics; when x =50% (Example 2) and x When the dielectric content reaches 70% (Example 3), the dielectric peak gradually broadens, frequency dispersion begins to appear, and the material exhibits stable piezoelectric constant and electrostrain properties over a wide temperature range of 25-300℃, indicating that a partially relaxor ferroelectric structure has been successfully constructed; when xWhen the dielectric temperature spectrum reaches 100% (Example 4), it exhibits typical characteristics of a relaxor ferroelectric material: broadened dielectric peaks and significant frequency dispersion (the position of the dielectric peaks shifts towards higher temperatures as the frequency increases). ε r ( T c ) / ε r The (RT) ratio decreased from 4.57 for normal ferroelectrics to 2.69. The material exhibits a flat dielectric response over an ultrawide temperature range of 25-500℃, with a relative permittivity change rate of less than 1%.
[0080] The above results indicate that by adjusting the fluoride ion doping concentration... x This allows for precise control over the degree of relaxation ferroelectric structure construction, thereby enabling KNN-based materials to transition from normal ferroelectric materials (… x =0%) to partially relaxed structure ( x =50%) to fully relaxed ferroelectric structures ( x A continuous structural transition (=100%). When x When the concentration is 30%, the dielectric temperature spectrum still exhibits the sharp peak shape of normal ferroelectrics, but the piezoelectric constant increases to 330 pC / N, and the Curie temperature rises to 330℃, indicating that this composition is in the precursor stage of the transition from normal ferroelectrics to relaxor ferroelectrics; when x When the dielectric constant is 100%, the material constructs a fully relaxor ferroelectric structure, exhibiting a flat dielectric response and excellent temperature stability over a wide temperature range of 25-500℃, making it suitable for wide-temperature-range dielectric devices and high-precision strain actuators.
[0081] Therefore, this invention utilizes the aforementioned anion-doped lead-free piezoelectric ceramic and its preparation and application. Using the constructed relaxor ferroelectric structure as a platform, by adjusting the degree of structure construction, customized design of functional properties over different wide temperature ranges can be achieved: partially relaxor structures ( x (50%~70%) exhibits excellent piezoelectric and strain temperature stability over a wide temperature range of 25-300℃: piezoelectric constant retention rates are 74% and 77%, respectively, and electro-strain retention rates are 72% and 78%, respectively; x Although the 30% structure is still a normal ferroelectric structure, it is in the pre-transformation stage, with the piezoelectric constant reaching its maximum value of 330 pC / N. This makes it suitable for applications requiring high piezoelectric performance and relatively low temperature stability. (Completely relaxed structure...) x =100%) has a flat dielectric response over an ultra-wide temperature range of 25-500℃, making it suitable for wide-temperature-range dielectric devices.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. An anion-doped lead-free piezoelectric ceramic, characterized in that: Lead-free piezoelectric ceramics have a relaxor ferroelectric structure constructed by anion doping; Its general chemical formula is 0.93K. 0.50 Na 0.44 Li 0.06 NbO3-0.07CaAO 3-x F 2x A is Zr. x The molar percentage of CaF2 replacing CaCO3, 0 < x ≤100%.
2. The method for preparing anion-doped lead-free piezoelectric ceramics as described in claim 1, characterized in that: Includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, lithium carbonate, niobium pentoxide, zirconium dioxide, calcium carbonate and calcium fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder. S2. The raw material powder obtained in S1 is pre-calcined at 750~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1080~1150℃ for 3~6h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
3. The method for preparing anion-doped lead-free piezoelectric ceramics according to claim 2, characterized in that: In both S1 and S2, the dispersion medium for the rolling ball mill was anhydrous ethanol, and the rolling ball milling time was 4-12 hours.
4. The method for preparing anion-doped lead-free piezoelectric ceramics according to claim 2, characterized in that: In S3, granulation is carried out by adding a polyvinyl alcohol solution to the calcined powder for granulation. The concentration of the polyvinyl alcohol solution is 6~10wt.
5. The method for preparing anion-doped lead-free piezoelectric ceramics according to claim 2, characterized in that: In S3, the pressing process involves using an electric tablet press to compress the granulated powder into tablets. The pressure of the electric tablet press is 8-12 MPa.
6. The method for preparing anion-doped lead-free piezoelectric ceramics according to claim 2, characterized in that: In S3, the temperature for discharging glue is 750-850℃, and the discharging time is 80-100 minutes.
7. The method for preparing anion-doped lead-free piezoelectric ceramics according to claim 2, characterized in that: In S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~6kV / mm, and the electric field polarization time is 20~40min.
8. The application of the anion-doped lead-free piezoelectric ceramic as described in claim 1, characterized in that: It is used in the fabrication of wide-temperature-range transducers.